IMPROVING SALES RATE THROUGH SOCIAL MEDIA MARKETING STRATEGY FOR SMALL BUSINESS - Novianti, Dian; Alamsyah, Alamsyah (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2023)
Social media emerged to be one of the business platforms nowadays, at first social media was introduced to connect people from around the world, the rising of technology and knowledge made people discover many methods and ways to conduct business, social media become one of the platforms to conduct business. The efficient of social media as business platform can be identify by many users, the minimum requirement of capital expense, the minimum effort of direct shipping, and social media business doesn’t require the shop owner to own a physical store, this advantage has made possibilities for countless people to conduct business even for those who have little to no capital resources. Nowadays the competition of business has become more and more by the day, one of many ways to survive the chance of bankrupt is to adapt. Small business especially MSMEs is often found in the village also in the city, therefore its is important to harness the potential of this aisle-based business for chance of improving household financial condition. The purpose of this study is to introduce and train locals to use social media as marketing platform and adapt to the business competition nowadays and ensure economic productivity.